Axiology of Modern Science: Navigating Ethical Dilemmas, Technological Imperatives, and Humanistic Benefits - Ade Sofa; Ahmad Syukri SS; Badarussyamsi (Darul Ilmi Bina Insan Foundation, 2024)
In an era characterized by rapid technological innovation, artificial intelligence expansion, and ecological crises, the development of science often prioritizes technical progress over moral considerations. This study critically examines the axiology of science as an essential philosophical framework to ensure scientific advancements remain aligned with human dignity and planetary sustainability. Utilizing a qualitative library research design with a philosophical-hermeneutic approach, this paper synthesizes contemporary and classical literature on the value dimensions of science. The analysis addresses three core issues: the structural alignment between axiology and scientific inquiry, the systemic factors leading to the marginalization of axiological reflection, and a critical evaluation of science's benefits alongside its potential risks. The findings demonstrate that axiology serves not merely as a moral supervisor, but as a active compass that bridges theoretical knowledge with human welfare, limits destructive applications, and promotes inclusive, data-driven public policy. However, the institutional dominance of positivism, hyper-specialization, and commercial pressures frequently sideline axiological considerations in modern research environments. The study concludes that embedding axiological evaluation into scientific education, policy design, and research governance is imperative for transforming scientific progress into sustainable, ethically grounded benefits for humanity.